Evaluation of alternative preservation treatments (water heat treatment, ultrasounds, thermosonication and UV-C radiation) to improve safety and quality of whole tomato - Pinheiro, Joaquina (2020)
Previously optimised postharvest treatments were compared to conventional chlorinated water treatment in terms of their effects on the overall quality of tomato (‘Zinac’) during storage at 10 °C. The treatments in question were water heat treatment (WHT = 40 °C, 30 min), ultrasounds (US = 45 kHz, 80 %, 30 min), thermosonication (TS =40 °C, 30 min, 45 kHz, 80 %) and ultraviolet irradiation (UV-C: 0.97 kJ m−2). The quality factors evaluated were colour, texture, sensorial analysis, mass loss, antioxidant capacity, total phenolic content, peroxidase and pectin methylesterase enzymatic activities, and microbial load reduction. The results demonstrate that all treatments tested preserve tomato quality to some extent during storage at 10 °C. WHT, TS and UV-C proved to be more efficient on minimising colour and texture changes with the additional advantage of microbial load reduction, leading to a shelf life extension when compared to control trials. However, at the end of storage, with exception of WHT samples, the antioxidant activity and phenolic content of treated samples was lower than for control samples. Moreover, sensorial results were well correlated with instrumental colour experimental data. This study presents alternative postharvest technologies that improve tomato (Zinac) quality during shelf life period and minimise the negative impact of conventional chlorinated water on human safety, health and environment.